2012
DOI: 10.12657/denbio.069.008
|View full text |Cite
|
Sign up to set email alerts
|

Xylem formation in Fagus sylvatica during one growing season

Abstract: Abstract:The study analyses the activity of cambium and the increment of wood during one growing season of European beech (Fagus sylvatica L.) in the central part (region) of the Drahanská vrchovina, Czech Republic. The research plot was situated at an altitude of 630 m a.s.l. The following parameters were studied: the beginning and end of cambial activity, differentiation of wood fibres and vessels and the total increment of wood during the growing season in six trees. Samples were taken during the growing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…The above findings are in accordance with recent studies on cambial phenology, confirming that precipitation is not a limiting factor during xylogenesis of beech within its natural distribution (Prislan et al 2018). A distinct trend between end of SCV and the upper asymptote, which could be considered as a proxy of the radial expansion of the stem, seems to be consistent with studies on xylem formation in beech (Čufar et al 2008;Vavrčík et al 2013;Semeniuc et al 2014). Nevertheless, the reversible shrinkage and expansion of the stem related to the changes in water content of outermost tissues should be taken carefully into account, when SCV amplitude is interpreted (Zweifel 2016).…”
Section: Inter-annual Scv In Relations To Climatesupporting
confidence: 92%
See 1 more Smart Citation
“…The above findings are in accordance with recent studies on cambial phenology, confirming that precipitation is not a limiting factor during xylogenesis of beech within its natural distribution (Prislan et al 2018). A distinct trend between end of SCV and the upper asymptote, which could be considered as a proxy of the radial expansion of the stem, seems to be consistent with studies on xylem formation in beech (Čufar et al 2008;Vavrčík et al 2013;Semeniuc et al 2014). Nevertheless, the reversible shrinkage and expansion of the stem related to the changes in water content of outermost tissues should be taken carefully into account, when SCV amplitude is interpreted (Zweifel 2016).…”
Section: Inter-annual Scv In Relations To Climatesupporting
confidence: 92%
“…Duration of SCV is mainly dependent on the end, and not onset, in SCV, which is partly reflected in the period of maximum cell production (Čufar et al 2008;Vavrčík et al 2013;Semeniuc et al 2014). In contrast, growth rate manifests an opposite, with later onset and earlier end observed with faster growth rate (Fig.…”
Section: Inter-annual Scv In Relations To Climatementioning
confidence: 99%
“…Similarly, Čufar et al (2008) observed maximum weekly production approximately in the first week of June in Slovenia at 400 m a.s.l. However, Vavrčík et al (2013) described maximum daily rates of wood production in European beech in the Czech Republic, at the same altitude as our study, in the second half of June 2010. This difference may be ascribed to the influence of specific weather and stand conditions on wood formation processes.…”
Section: Stem Growth Increment and Stem Volume Changessupporting
confidence: 68%
“…Additionally, the temperature impact combined with that of AWR. Vavrčík et al (2013) also highlighted the impact of temperature and AWR on the onset of cambial activity in European beeches growing in the same area. According to our research, leaf yellowing was usually observed in October/early November.…”
Section: Climate-leaf Phenology Relationshipmentioning
confidence: 94%
“…The monthly and seasonal means of the previous years and the years of tree-ring formation (referred to as "the given year") were considered. The period from March to August should exert the highest influence on the radial growth in this area (Vavrčík et al 2013). Climate-leaf phenology relationships were determined using Pearson's correlation coefficient to reveal the most significant climate factors (monthly or seasonally) for tree growth and phenological phases from 1992-2011.…”
Section: Analysis Of the Climate-leaf Phenology-tree-ring Width Growtmentioning
confidence: 97%